Stability Analysis and Voltage Control in the Power System Based on the Hybrid Automata Model - Fariba Forouzesh; Mahdiyeh Eslami; Mehdi Jafari Shahbazzadeh (International Transactions on Electrical Energy Systems)
This paper proposes a systematic method using the hybrid automata (HA) model for supervisory management design of power systems to increase stability. The HA model monitors the behavior of the power system and derives a model from which the system’s stability is evaluated. In the modeling framework, the hybrid system formalism regulates continuous dynamics and discrete switching behavior. The proposed method extracts a system’s control graph, state space, and transfer function, facilitating voltage stability evaluation. A discrete event system (DES) is employed to manage disturbances resulting from load surges, generator outages, capacitor banks, and under-load tap changer (ULTC) transformers. The ULTC transformer and the capacitor bank are utilized to examine the feasibility and effectiveness of the proposed supervisory controller design approach in the presence of distributed generation (DG). Simulation results showed the effectiveness of the HA-based supervisory controller in improving the control and voltage stability, as demonstrated by the generator rotor angle and bus voltage responses, power system eigenvalues, and the stability theorem of linear switching systems. The proposed method provides a promising solution for managing power system stability.